The Use of 16s RNA AND NODC Gene Sequence in Resolving The Phylogenetic Relationship of Rhizobia Associated With Paraserianthes falcataria (L.) Nielsen Plant - Prana, Titik K.; Sone, Teruo; Nakagawa, Hiroko Kawasaki; Yokota, Atsushi; Seki, Tatsuji; Tomita, Fusao (ANNALES BOGORIENSES, 2004)
Studies on genet ic position of several iso lates liv ing symbiot i a lly on ParaseriCllltli esfalcalaria have been carried out using amplification and se uenc ing tec hni ques of 16S rDNA and specific gene fo r nodulation (/lode) . The "p hylogenetic LTee" cons tructed based On 165S rONA showed that rh izobia growing symbiotically on Paraserianthes fa/ca taria consisted f 3 group . TIl . fi r t group, was fasl- growing rhIzobia wh ich have close r lationshlp to Rhizobium tropicii, the second and the third groups were slow-growing r!lI zobia wh ic h have c lose relationsh ip to Bradyrhizobillnl elkanJi and B j aponiclIfll. However, the "phy logenetic tTee" constructed on the ba is of part ln l ll odC gene md icatcd the existence of an JIldependen t group, si nce they did not show any siglU tica nt degree of relationsh ip w ith the ex isting groups. T hi s was also supported by diffi rences in pby iological characteri tiC i.e Indole Ace ti c Acid productIOn and salt tolerance of the iso lates . These differe nces shows uS that "direct _equenc ing" method of certain specdic genes coul d give a more specific re ult tha n ou ld di p lay more clearly the degree of relat ionship at species leve l.